Perancangan Fakultas Kedokteran Gigi Universitas Riau Dengan Pendekatan Arsitektur Kontekstual - Vini Asfarilla; Yohannes Firzal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Oral and dental health are not very much paid attention to as most people failed to realize the importance of them. Increasing need for dental health institutions can be regarded as an indicationof raise public awareness of dental and oral health conditions. Therefore, it needs qualified human resources in order to provide optimal the health services. Faculty of Dentistry of University of Riau which is offered is coresponding with aplication of Contextual Architecture approach, that is a building should have connection with surroundings and keep preserving the environmentcharacteristic. Through the Architecture theme, the concept of Harmony Collaboration is defined as a collaboration between dental functions and the principle of Harmonic Contextual. The concept is applied to site pattern, mass formation, and facade. The site designed pattern is based on teeth formation, the mass of building is based on the principle of the harmonious to the surrounding buildings. The building facade designed is based on the form of teeth pattern.Keywords: Dental, Faculty of Dentistry, Contextual Architecture, Harmony Collaboration